(x+1)(x—3)+4 因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 06:44:43
(x+1)(x—3)+4因式分解(x+1)(x—3)+4因式分解(x+1)(x—3)+4因式分解(x+1)(x-3)+4=x^2-2x-3+4=x^2-2x+1=(x-1)^2你8年纪吗你哪的?X2+
(x+1)(x—3)+4 因式分解
(x+1)(x—3)+4 因式分解
(x+1)(x—3)+4 因式分解
(x+1)(x-3)+4
=x^2-2x-3+4
=x^2-2x+1
=(x-1)^2
你8年纪吗
你哪的?
X2+2X-3+1=(X+1)2
(x+1)—4x因式分解
(x+1)(x—3)+4 因式分解
(x+4)(x-1)-3x 因式分解
因式分解:x³-x²-6x 因式分解:(x+1)(x-2)-4
(x—1)(x—3)+1因式分解
因式分解:(x+1)(x+2)(2x+3)(x+6)-20x^4
a3+2a2b+3ab2+6b3 因式分解(x+1)(x+2)(x+3)(x+4)+1因式分解
(x-1)(x+1)(x+3)(x+5)+1 因式分解快 因式分解
x^4-x^3-x-1因式分解
x^4-x^3-x-1因式分解
x^3-4x^2-4x-5(因式分解)
因式分解:(x+3)(x²-1)(x+5)-9
(x+1)(x+2)(x+3)(x+4)+1怎么因式分解?
(x+1)(x+2)(x+3)(x+4)-24 因式分解
(x+1)(x+2)(x+3)(x+4)-24 十字相乘因式分解
将下列式子 (x+1)(x+2)(x+3)(x+4)+1因式分解
(1)x^2-4x+3 (2) x^2-2x+1 各因式分解 ?
(x+1)(x+2)(x+3)(x+4)-15 (因式分解)